Pengaruh Mordan Tawas, Tunjung dan Kapur Sirih Terhadap Hasil Pencelupan Kain Katun Mori Primissima dengan Ekstrak Daun Gambir (Uncaria Gambir Roxb) - Gustiani, Nurulita; Novrita, Sri Zulfia; Adriani, Adriani (Universitas Batanghari Jambi, 2024)
Utilization of abscission (deciduous) plants which have the potential to be extracted as natural dyes that are non-toxicand environmentally friendly. This research aims to describe the name of the color (hue), the darkness of the color (value), thecolor resistance/fading to washing and the influence of the differences between tawas, tunjung and kapur sirih mordants on theresults of dyeing gambier leaf extract on cotton. The type of research is experimental research. The object of this research isprimissima mori cotton dipped in gambier leaf extract (Uncaria Gambir Roxb) with alum, tunjung and whiting mordant. Usingprimary data with data collection techniques through questionnaires sourced from 18 panelists consisting of 3 lecturers who havetaught textile courses and 15 Fashion Design students from the IKK Department. The collected data was processed in the form offrequency percentages and analyzed using the Friedman K-Related Sample test with SPSS version 29. This research produces thename of the color (hue), dark and light color (value) and color resistance/fading to washing. Without using a mordant, the colorMuddy Waters Brown #B19453 is produced, the value is very bright and the color/fading resistance to washing changes/reduces.Dyeing with tawas mordant produces the color Muddy Waters Brown #8D774E, the value is quite bright and the colorfastness/fading changes/reduces slightly. Tunjung Mordan shows the color Soft brown #554736, the value is not light and thecolor does not change at all. And with kapur sirih mordant produces the color Muddy Waters Brown #98815C, the value is brightand the color changes/reduces slightly. The Friedman K-Related Sample test for dark and light colors (value) is a significantvalue < significance level = 0.001 < 0.05 with the result that Ha is accepted and Ho is rejected. Where Ha states that there is asignificant influence on the lightness and darkness of the color (value). Based on the analysis of the Friedman K-Related Sampletest for color resistance/fading to washing, it is significant < significance level = 0.001 < 0.05. So Ho is declared rejected,meaning that there is a significant difference in color resistance/fading to washing caused by differences in mordant on the resultsof dyeing gambier leaf extract (Uncaria Gambir Roxb) on cotton fabric